Estimation of ecosystem metabolism from diel oxygen technique in a saline shallow lake: La Salada (Argentina) - Alfonso, María Belén (2014)
Studies based on continuous monitoring of diel changes in dissolved oxygen concentration allow the estimation of ecosystem metabolism and provide a measure of the overall trophic processes of an ecosystem. In this study, net ecosystem production (NEP), community/ecosystem respiration (R), and gross primary production (GPP) rates were estimated in relation to physicochemical and climatic variables for 18 months in La Salada, a saline shallow lake. Net autotrophic conditions prevailed during the study period (NEP: 64.05 ± 44.22 mmol O2 m−2 day−1). GPP and R were positively correlated and were synchronized on a daily timescale, with GPP typically greater than R. Principal component analysis revealed that monthly rates of GPP, R, and NEP responded, as expected, to temperature and light seasonal patterns. Water level and conductivity fluctuations, because of evapoconcentration and water management, were relevant as a driver of the physicochemical and biological characteristics of the lake. In saline lakes as La Salada, an adequate management of water resources will be relevant to maintain the ecosystem equilibrium and the quality of its resources.